Warming, temperature fluctuations and thermal evolution change the effects of microplastics at an environmentally relevant concentration. (1st January 2022) - Chang, Mengjie; Zhang, Chao; Li, Mingyang; Dong, Junyu; Li, Changchao; Liu, Jian; Verheyen, Julie; Stoks, Robby
Abstract: Microplastics are sometimes considered not harmful at environmentally relevant concentrations. Yet, such studies were conducted under standard thermal conditions and thereby ignored the impacts of higher mean temperatures (MT), and especially daily temperature fluctuations (DTF) under global warming. Moreover, an evolutionary perspective may further benefit the future risk assessment of microplastics under global warming. Here, we investigated the effects of two generations of exposure to an environmentally relevant concentration of polystyrene microplastics (5 μg L −1 ) under six thermal conditions (2 MT × 3 DTF) on the life history, physiology, and behaviour of Daphnia magna . To assess the impact of thermal evolution we thereby compared Daphnia populations from high and low latitudes. At the standard ecotoxic thermal conditions (constant 20 °C) microplastics almost had no effect except for a slight reduction of the heartbeat rate. Yet, at the challenging thermal conditions (higher MT and/or DTF), microplastics affected each tested variable and caused an earlier maturation, a higher fecundity and intrinsic growth rate, a decreased heartbeat rate, and an increased swimming speed. These effects may be partly explained by hormesis and/or an adaptive response to stress in Daphnia . Moreover, exposure to microplastics at the higher mean temperature increased the fecundity and intrinsic growth rate of cold-adapted high-latitude Daphnia, but not of the warm-adapted low-latitude Daphnia, suggesting that thermal evolution in high-latitude Daphnia may buffer the effects of microplastics under future warming. Our results highlight the critical importance of DTF and thermal evolution for a more realistic risk assessment of microplastics under global warming. Highlights: MP did not change life history and behaviour under standard thermal conditions. MP changed all tested variables under challenging thermal conditions. A 4 °C increase in MT enhanced the effects of MP on intrinsic growth rate. 5 °C DTF enhanced the effects of MP on fecundity and intrinsic growth rate. Thermal evolution buffered the effects of MP under warming.